All Days 2010
DOI: 10.2118/137986-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Seismic Anisotropy Analysis on Multi-Azimuth OBC Seismic Data in an Offshore Carbonate Oil Field, U.A.E.

Abstract: Fractures can be observed in micro or macro scale at outcrops and many oil/gas reservoirs can be fractured as well. A good understanding of the fracture network is hence critical for reservoir development since it could have significant impact on fluid flow. Full azimuth 3D seismic data provides a means of detecting and characterizing fractures before drilling. Seismic anisotropy investigation for fracture detection has been carried out in a carbonate oil field located in offshore United Arab Emirates (U.A.E).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This may explain the stacked anisotropy anomalies that are observed in Figure 6. Overburden effects have been noted by Liu et al (2011); Ikawa and Mercado (2010); and Luo et al (2007). Note that in a recent publication, Liu et al (2015) have performed 3D synthetic study of estimating the fracture density of small-scale vertical fractures when large-scale vertical fractures are present.…”
Section: Diffuse Fractures Vs Fracture Corridorsmentioning
confidence: 92%
See 1 more Smart Citation
“…This may explain the stacked anisotropy anomalies that are observed in Figure 6. Overburden effects have been noted by Liu et al (2011); Ikawa and Mercado (2010); and Luo et al (2007). Note that in a recent publication, Liu et al (2015) have performed 3D synthetic study of estimating the fracture density of small-scale vertical fractures when large-scale vertical fractures are present.…”
Section: Diffuse Fractures Vs Fracture Corridorsmentioning
confidence: 92%
“…We can either use azimuth velocity-based attributes (low resolution) or azimuth amplitudebased attributes (high resolution) to infer relative anisotropy magnitude (a proxy for fracture intensity) and anisotropy orientation (a proxy for fracture orientation). In our previous study (Liu et al, 2011), azimuthal amplitude variation was used, and we found that the overburden effect was identified as one of the major influencing factors affecting the reliability of fracture interpretation in the targets (Ikawa and Mercado, 2010;Liu et al, 2011). The seismic anisotropy magnitude was computed over intervals for the major reservoirs defined by the seismic interpretation surfaces.…”
Section: Seismic Anisotropymentioning
confidence: 99%